Controle de velocidade aplicado a um sistema de acionamento com motor de relutância variável - Sobreira, Fernando Barros (2008)
This work presents studies and practical implementations of a speed control driver for a switched reluctance motors. The work begins with a literature review on the system drive of the machine, aspects of identification and control of the current and speed loops are addressed. Based on literature review, it describes the basic elements in the practical implementation of the system composed of a static power conversion, conditioning system and data acquisition, the switched reluctance motor and the load. Theoretical and practical aspects of the current and speed loops are treated. The current loop was implemented with a PI controller in a structure of self-tuning based on the introduction of a non-linearity of the relay type, positioned in the control loop for the purpose of identifying the dynamics of the current loop. Special interest was given to speed control implemented through a structure that allows the RST with a combination of least squares estimator to identify the dynamics of the speed loop. Considerations of loop stability are established. Due to the speed required for the processing of polynomials of control, was used a hardware structure suitable for the processing of digital signals. The system is mounted on the laboratory GPAR (Research Group on Automation and Robotics).